Polymerisation shrinkage of light-cured hydroxyapatite (HA)-reinforced dental composites - (:unkn) unknown (My University, 2010)
The dental composites are preferably used as filling materials due to their esthetic appearances. Nevertheless one of the major problems, during the application of the dental composites, is shape change named as "polymerisation shrinkage" affecting clinical success of the dental restoration while photo-polymerisation. Polymerisation shrinkage of composites arises basically from the formation of a polymer due to the monomer transformation which composes of an organic matrix phase. It was sought, throughout this study, to detect and evaluate the structural polymerisation shrinkage of prepared dental composites in order to optimize the effects of various fillers included in hydroxyapatite (HA)-reinforced dental composites and hence to find a means to modify the properties of these dental composites prepared with defined parameters. As a result, the shrinkage values of the experimental dental composites were decreased by increasing the filler content of composites and the composition of different fillers used had effect on the shrinkage of the prepared composite systems.
Keywords: BisGMA; Dental composites; Hydroxyapatite (HA); Shrinkage